2014
DOI: 10.1111/jorc.12101
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Motivation: A New Modifiable Risk Factor for Peritonitis in Patients Undergoing Peritoneal Dialysis?

Abstract: Lack of motivation predicted peritonitis particularly if associated with depression. Further studies are required focusing on specific motivation scoring schemes and the psychosocial support that might lead to better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
13
0
4
Order By: Relevance
“…Patients with CKD were aware of the consequences associated with non‐adherence to integrated management, and these findings are supported by Ghimire et al () Physiological consequences of non‐adherence to integrated management include pulmonary and peripheral edema, septicemia, dosage adjustment, peritonitis (patients undergoing CAPD), readmissions, elevated urea and electrolytes, weakness of bones, and changes in treatment plans, which ultimately increases the cost of medical care, thus exacerbating the economic burden (Paudel et al, ; Tannor et al, ). Furthermore, poor adherence has been cited as causing reduced lifespan of patients with CKD, and consequently increased mortality, as well as faster progression to late stages of CKD for those in the early stages.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Patients with CKD were aware of the consequences associated with non‐adherence to integrated management, and these findings are supported by Ghimire et al () Physiological consequences of non‐adherence to integrated management include pulmonary and peripheral edema, septicemia, dosage adjustment, peritonitis (patients undergoing CAPD), readmissions, elevated urea and electrolytes, weakness of bones, and changes in treatment plans, which ultimately increases the cost of medical care, thus exacerbating the economic burden (Paudel et al, ; Tannor et al, ). Furthermore, poor adherence has been cited as causing reduced lifespan of patients with CKD, and consequently increased mortality, as well as faster progression to late stages of CKD for those in the early stages.…”
Section: Discussionmentioning
confidence: 82%
“…Other motivators of adherence in patients with CKD include being aware of the consequences and severity of symptoms, such as deterioration in health, fear of death, positive interaction with the health-care team (Ghimire et al, 2017), and the use of evidence-based practice to encourage fluid restriction (Jia, Huang, Chu, Lu, & McArthur, 2016). Lack of motivation has been found to be a risk factor for complications, such as peritonitis, in patients with CKD undergoing peritoneal dialysis (Paudel, Namagondlu, Samad, McKitty, & Fan, 2015). Poor adherence in CKD population creates severe complications, coupled with increased mortality and morbidity rates (Ahlawat, Tiwari, & D'Cruz, 2016).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…To reduce peritonitis risk, we traditionally focus on patient training, although there is diminishing return to intensification of a training scheme; potential improvement of patient technique needs to be counterbalanced against increasing risk of patient burnout. In fact, in a retrospective study, we were unable to find an association between peritonitis risk and ‘exchange technique’ . There are theoretical reasons to believe that fluid overload may be a modifiable risk factor for peritonitis; patients with severe fluid overload may develop bowel wall oedema and ischaemia .…”
Section: Introductionmentioning
confidence: 79%
“…In fact, in a retrospective study, we were unable to find an association between peritonitis risk and 'exchange technique'. 6 There are theoretical reasons to believe that fluid overload may be a modifiable risk factor for peritonitis; patients with severe fluid overload may develop bowel wall oedema and ischaemia. 7 This may lead to an increased gut permeability causing high circulating endotoxaemia.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients on APD lived in institutional households, and the caregiver was not a relative; all of these patients had at least one peritonitis episode, suggesting that there may be a relationship between peritonitis and emotional, social, and psychological factors in this setting. This may affect patient situation as is shown in one study where lack of motivation was reported as a modifiable predictor factor of peritonitis [23].…”
Section: Discussionmentioning
confidence: 99%